Biodiversity of Crabs in Karwar Mangrove Environment West Coast of India - V.S.Kakati, Pradnya D.Bandekar, Kusuma Neelkantan (Recent Research in Science and Technology, 2011)
In this study, the distribution of crabs in Karwar was recorded from October 2007 to July 2008. At monthly intervals. The species present on the subs tram and on the vegetation area were recorded in quadrant each measuring 1meter square. There are about 15 crabs species are distributed in karwar mangrove environment. Crabs belonging to the family Grapsidae and Ocypodidae are most dominant forms. Substrate suitability, effects of tidal inundation and distribution of mangrove plants were the possible factors that could influence zonaztion and abundance of the crabs in the karwar mangroves.